A Critique of Industrial Relations Theory - Hameed, Syed (Relations industrielles / Industrial Relations, 1982)
The author critically examines theoretical developments in industrial relations. Pluralism, the Systems approach and the radical perspectives are identified as the main contributions to the stream of thought in industrial relations theory.